Role of Organizational Creativity in the Development of Public Organizations, with the application of autonomous public institutions in the Hashemite Kingdom of Jordan - Tubaishat , Nawaf (The Arab Journal of Administration, 2020)
This study aimed at analyzing the concept of organizational creativity and explaining how it is applied in the development of public organizations, as well as identifying the elements and constraints of organizational creativity, and what are the areas of benefiting from organizational creativity in developing Jordanian autonomous public institutions. The study population may consist of the administrative leaderships in the Jordanian public organizations, and the leadership groups were approved at the level of the chairman, directors, general managers, supervisors, managers, and even department heads. The study concluded that creativity organizational contribute greatly to the development of autonomous public institutions of Jordan, the study showed that innovation organization plays a distinct role in the development of public organizations in the development of autonomous public institutions, as well as a range of ingredients that must be met for the creativity of organizational structure, and also study showed that Organizational innovation is facing a wide range of obstacles that prevent the benefit from it in the workplace. The study recommended the necessity of increasing the awareness of administrative leaders about the role of organizational creativity in the process of developing organizations by making use of the creations of workers. In addition to the necessity of reformulating the foundations of organizational creativity and dividing them into groups, and adding new elements to those already existing to reach a higher proportion of these constituents, to know exactly the main and essential elements of creativity in organizations, and trying to get rid of obstacles to benefit from the creativity of workers in the development of organizations.